Assessing Longitudinal Relationships among Thwarted Belongingness, Perceived Burdensomeness, and Eating Disorder Symptoms. Issue 6 (7th February 2019) - Trujillo, Alejandro; Forrest, Lauren N.; Claypool, Heather M.; Smith, April R.
Abstract : Objective: Past work has documented a cross‐sectional relationship between eating disorders (ED) and suicidality, but few studies have examined the directionality of this relationship. Informed by the interpersonal–psychological theory of suicide (IPTS), this study examines the bidirectional, longitudinal relationship between ED symptoms and two determinants of suicide ideation—thwarted belongingness (TB) and perceived burdensomeness (PB). Method: Ninety‐two treatment‐seeking individuals with ED (94.5% White, 95.6% female) completed baseline (T1) measures of ED symptoms along with TB and PB. Of those, 75 (81.5%) completed a follow‐up assessment eight weeks later (T2). Results: Separate linear regression models revealed that T1 ED symptoms did not predict T2 TB ( b  =   .03, p  =   .42) or T2 PB ( b  =   −.01, p  =   .68). Similarly, T1 TB did not predict T2 ED symptoms ( b  =   .25, p  =   .37). T1 PB did significantly predict T2 ED symptoms ( b  =   0.52, p  =   .04). Further, among participants with AN/sub‐AN, T1 TB and PB predicted T2 ED symptoms ( p 's ≤ .03). Conclusion: Our results reveal the need for a nuanced understanding of the relationship between ED and suicidality. This study found that PB predicts greater ED symptoms and, among the AN/sub‐AN sample, TB does as well.